A Working Hypothesis on Vesicular Lesions Related to COVID-19 Infection, Koebner Phenomena Type V, and a Short Review of Related Data - Tatu AL; Baroiu L; Fotea S; Anghel L; Drima Polea E; Nadasdy T; Chioncel V; Nwabudike LC (Dove Medical Press, 2021)
Alin Laurentiu Tatu,1,2,* Liliana Baroiu,3,4,* Silvia Fotea,4,5,* Lucretia Anghel,6,7 Eduard Drima Polea,6,8,* Thomas Nadasdy,1 Valentin Chioncel,9,* Lawrence Chukwudi Nwabudike10 1Dermatology Department, “St. Parascheva” Clinical Hospital of Infectious Diseases, Galati, Romania; 2Faculty of Medicine and Pharmacy, Clinical Medical Department, Dermatology, Medical and Pharmaceutical Research Unit, Competitive, Interdisciplinary Research Integrated Platform, ReForm-UDJG “Dunărea de Jos” University, Galati, Romania; 3Infectious Diseases Department, “St. Parascheva” Clinical Hospital of Infectious Diseases, Galati, Romania; 4Faculty of Medicine and Pharmacy, Clinical Medical Department, “Dunărea de Jos” University, Galati, 800010, Romania; 5Sf Ioan Clinical Hospital of Pediatrics, Galati, Romania; 6Department of Clinical Medicine, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University, Galați, 800010, Romania; 7Internal Medicine Department, Sf Andrei Clinical Emergency Hospital, Galati, Romania; 8Elisabeta Doamna Clinical Hospital of Psychiatry, Galati, Romania; 9Department of Cardio-Thoracic Pathology, Faculty of Medicine, ‘Carol Davila’ University of Medicine and Phamacy, Bucharest, 050474, Romania; 10N. Paulescu National Institute of Diabetes, Bucharest, Romania*These authors contributed equally to this workCorrespondence: Thomas NadasdySpitalul Clinic de Boli Infectioase “Sf. Cuvioasa Parascheva”, Str. Traian, Nr. 393, Galati, 800179, RomaniaTel +40 751609000Email thomas.nadasdy@gmail.comLucretia AnghelFacultatea de Medicină și Farmacie, Str. Al. I. Cuza Nr. 35, Galati, 800216, RomaniaTel +40 740050224Email anghel_lucretia@yahoo.comAbstract: SARS-CoV-2 has recently been associated with the reactivation of varicella zoster virus in patients. This is potentially an observation of a local susceptibility of the skin in areas of vesicle formation. This article explores the dermatologic manifestations that have been linked to the SARS-CoV-2 virus, their infectious risk, as well as potential confounding factors. An isotopic response may be occurring due to the occurrence of an immunocompromised district incited by sustained inflammation mediated by inflammatory cytokines.Keywords: COVID-19, SARS-CoV-2, Koebner phenomenon, wolf isotopic response, locus minoris resistentiae, vesicular rash